MINAT DAN MOTIVASI BELAJAR MATEMATIKA SISWA PADA PENDEKATAN CULTURALLY RESPONSIVE TEACHING (CRT): A SYSTEMATIC LITERATURE REVIEW - Pradiarti, Refni Adesia (Jurnal MIPA dan Pembelajarannya, 2025)
Students' interest and motivation in learning mathematics remain a challenge in the field of education. One approach that can be implemented to enhance student engagement is Culturally Responsive Teaching (CRT), which emphasizes the integration of students' cultural backgrounds into the learning process. This approach aims to create a more relevant and meaningful learning experience by connecting mathematical concepts with local cultural contexts. This study seeks to analyze the effectiveness of CRT in improving students' interest and motivation in learning mathematics through a Systematic Literature Review (SLR) of articles discussing CRT implementation in mathematics education. The findings from the literature analysis indicate that Culturally Responsive Teaching (CRT) has been proven effective in enhancing students' interest and motivation in learning mathematics. The success of this approach lies in its ability to create culturally relevant learning, increase student engagement, and foster a more enjoyable and meaningful learning environment.